Do Algorithms Have Cosmopolitics? A Discussion Based On Facebook's Nudity Policy - Jurno, Amanda; d'Andréa, Carlos (AoIR Selected Papers of Internet Research, 2017)
Discussions about algorithmic mediation on Facebook are becoming increasingly evident due to the controversies triggered by the policies of this platform. In this article we take a closer look at the frequent processes of censorship of images containing traces of nudity. Our objectives are to discuss the relations of power and knowledge associated with the algorithms (Introna 2016, Gillespie, 2014) to whom are delegated the power to decide to circulate or not a given content, as well as to problematize, using the concepts of cosmopolitanism and cosmopolitics (Latour, 2004), the different public reactions and institutional responses to Facebook’s censorships. For this purpose, we focus on two cases of censorship held in the platform in 2016: 1) the exclusion of the documentary photo "The Terror of War", published, among other pages, by the Norwegian newspaper AftenPost and; 2) the exclusion of an image of an Amazonian Yawalapiti Indian with naked breasts, published by the Brazilian magazine Piseagrama on its page. In the first case, the restriction of the circulation of the Vietnam War's famous photograph provoked a wide international repercussion, which, in brief, demanded from Facebook to respect the "cosmopolitan" values of contemporary Western society, like “freedom of speech”. On the other hand, the almost silent censorship of the image of the Brazilian Indian reinforces not only the invisibility of the indigenous cause in this country, but also signals an apparent inability of these algorithms and of the public associated to them to recognize non-Eurocentric cosmopolitics.